Diagnóstico prenatal y resultados perinatales en recién nacidos con atresia esofágica - Huertas-Tacchino, Erasmo (2024)
Introduction: Esophageal atresia is a rare congenital malformation of the digestivesystem. Early diagnosis is essential to plan adequate medical and surgical treatments.Objective: To evaluate the diagnosis of esophageal atresia using prenatal ultrasoundand to describe the perinatal outcomes associated with this pathology. Methods:Descriptive, retrospective study of newborns with confirmed esophageal atresiaseen at the Instituto Nacional Materno Perinatal (INMP) between 2019-2021.Data were collected on medical and ultrasound diagnoses, as well as maternaland neonatal variables. The procedures were approved by the institution's ethicscommittee. The information was kept confidential using alphanumeric codes, and acoded and restricted database was created for analysis. Results: There were 46,301births at the INMP. Eighteen cases of confirmed esophageal atresia were identified(3.9 per 10,000 births). It was found that 66.7% of cases with esophageal atresia hadsome other associated malformation, cardiac being the most frequent. Intrauterinegrowth restriction (66.6%) and polyhydramnios (55.5%) were the most commonfindings in prenatal ultrasounds. Mortality was 50%, but only 20% when excludingfetuses with malformations. Conclusions: In neonates with confirmed esophagealatresia, intrauterine growth restriction was the most frequent ultrasound finding.Polyhydramnios and small or absent stomach were observed in about 50% ofthe cases, so their absence does not exclude the possibility of this pathology.The incidence of associated malformations was similar to that reported in otherpublications, but infant mortality was higher even after excluding malformed fetuses.